A qualitative exploration of knowledge of Chagas disease among adolescents in rural Ecuador - Patricia Mora-Criollo; Majo Carrasco-Tenezaca; Sharon Casapulla; Benjamin Bates; Mario Grijalva (Rural and Remote Health, 2023)
Introduction: Chagas disease (CD) is a neglected tropical disease that affects 6 to 7 million people worldwide. In South America, CD is a major health problem in several regions, causing more than 12 000 deaths per year. CD is caused by a parasite called Trypanosoma cruzi, mostly transmitted through the contaminated feces of certain species of triatomine bug, commonly known as the 'kissing bug'. CD is endemic in Loja province in the southern region of Ecuador, where triatomines have been found in 68% of communities. Previous promotion of healthy practices in Loja province have included educational programs directed toward youth to affirm cultural and social norms that support health and prevent CD transmission. The present study was designed to evaluate current knowledge related to CD among youth in the three communities of Loja province following previous intervention programs. Methods: A descriptive, qualitative approach was applied using individual semi-structured interviews with 14 young people (eight females, six males) from three rural communities in Loja province. Interviews assessed knowledge about CD transmission, knowledge about the parasite-vector-disease pathway, and the role of youth in preventing Chagas disease in their communities. Results: Following a thematic analysis of the data, the study results showed there is cursory knowledge of the triatomine insect that can carry the causative parasite for CD. Participants were able to generally talk about the vector, habitat and prevention practices for triatomine infestation. Nevertheless, limited understanding of transmission dynamics in the parasite-vector-disease pathway itself was found. One major finding was that prevention practices were not correctly applied or followed, increasing the risk of exposure in the community. Youth also articulated that CD is stigmatized in their communities, which may be a barrier for prevention efforts. Conclusion: Gaps in knowledge about the parasite-vector-disease pathway were identified among youth. Overall, youth responses indicated positive regard for prevention practices and a desire to be involved in prevention programs. Developing educational programs focusing on CD transmission may be needed to improve control and prevention of this parasitic disease. The implications of these findings are discussed for developing effective control programs in the region.